2014
DOI: 10.1002/ejic.201402844
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Microwave Dielectric Properties of Ultralow‐Temperature Cofirable BaV2O6 Ceramics

Abstract: A new ultralow-temperature-sinterable BaV 2 O 6 ceramic was prepared through a conventional solid-state ceramic method. Thermogravimetric and differential-scanning-calorimetry analyses were performed to confirm the phase formation of BaV 2 O 6 . Phase purity and crystal structure of the ceramic material were studied by using X-ray diffraction analysis and Raman spectroscopic studies. BaV 2 O 6 crystallizes in an orthorhombic unit cell, and the calculated lattice parameters are a = 8.532 Å, b = 12.583 Å, and c … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…3. The vibration modes in the Raman spectra of the Ca 5 Mn 4 (VO 4 ) 6 ceramics are classified into two groups, internal and Raman band observed in the 912 cm -1 can be assigned to the internal symmetric stretching vibration of (VO 4 ) 3-ions, whereas the Raman bands in the 900-750 cm -1 region can be identified as the internal anti-symmetric stretching vibration of (VO 4 ) 3-ions [3,15]. The symmetric bending vibrations of (VO 4 ) 3-anions are observed in the region between 470 and 300 cm -1 [16].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3. The vibration modes in the Raman spectra of the Ca 5 Mn 4 (VO 4 ) 6 ceramics are classified into two groups, internal and Raman band observed in the 912 cm -1 can be assigned to the internal symmetric stretching vibration of (VO 4 ) 3-ions, whereas the Raman bands in the 900-750 cm -1 region can be identified as the internal anti-symmetric stretching vibration of (VO 4 ) 3-ions [3,15]. The symmetric bending vibrations of (VO 4 ) 3-anions are observed in the region between 470 and 300 cm -1 [16].…”
Section: Methodsmentioning
confidence: 99%
“…Especially, advanced substrate materials with a low dielectric constant (e r ), a high quality factor (Q 9 f), and a near-zero temperature coefficient of resonant frequency (s f ) are receiving increased interest [1,2]. In addition, the low temperature cofired ceramic (LTCC) technology has been widely investigated due to significant benefits over other established packaging technologies for low-cost and miniaturization in the microwave devices [3,4]. To meet the requirement of LTCC technology, the materials must have lower sintering temperature than the melting point of Ag electrode (960°C).…”
Section: Introductionmentioning
confidence: 99%
“…have been investigated for LTCC applications. However, several attempts have been also made to identify new vanadium based compounds, including BaV 2 O 6 , SrV 2 O 6 , LiMgVO 4 , etc. with ultra‐low firing temperature which makes them suitable candidates for ULTCC applications.…”
Section: Introductionmentioning
confidence: 99%
“…In a study regarding investigation of microwave dielectric properties of the CaV 2 O 6 ceramic, Yao et al synthesized this ceramic using a solid‐state reaction method and reported that the sample sintered at 675°C represented microwave dielectric properties of ε r = 10.2, a high‐quality factor (Q × f) of 123 000 GHz (at 10.2 GHz) and a negative τ f of −63 ppm/°C, but chemical compatibility of this ceramic with electrode materials has not been investigated. According to another report about one of the other vanadium based ceramics, the BaV 2 O 6 ceramic sintered at 550°C exhibited microwave dielectric properties of ε r = 11.2, Q × f=42 790 GHz, and τ f =28.2 ppm/°C (a positive τ f compared with CaV 2 O 6 ) . On the other hand, recent evidences have proved that the formation of solid solutions by ionic substitution and various dopants is an effective approach to decrease the sintering temperature and to address the large positive or negative temperature coefficient of frequency ( τ f ), constructing a material with good thermal stability .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation